2021
DOI: 10.3390/genes12091405
|View full text |Cite
|
Sign up to set email alerts
|

The Role of De Novo Variants in Patients with Congenital Diaphragmatic Hernia

Abstract: The genetic etiology of congenital diaphragmatic hernia (CDH), a common and severe birth defect, is still incompletely understood. Chromosomal aneuploidies, copy number variations (CNVs), and variants in a large panel of CDH-associated genes, both de novo and inherited, have been described. Due to impaired reproductive fitness, especially of syndromic CDH patients, and still significant mortality rates, the contribution of de novo variants to the genetic background of CDH is assumed to be high. This assumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…None of the major reviews on this topic recognize this curious association. [17][18][19][20] Among the patients of cutis laxa, CDH has also been reported in ARCL-1A and ARCL-1B; but the frequency seldom exceeds 10%. [4] Thus, the high frequency of 57% makes CDH a characteristic clinical feature of URDS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the major reviews on this topic recognize this curious association. [17][18][19][20] Among the patients of cutis laxa, CDH has also been reported in ARCL-1A and ARCL-1B; but the frequency seldom exceeds 10%. [4] Thus, the high frequency of 57% makes CDH a characteristic clinical feature of URDS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to LTBP-4 gene, more than 2 dozen genes such as FBN1, FBLN4 and FBLN5 also take part in normal elastogenesis. [19][20][21] We hypothesize that the nature of gene mutations might be responsible for site-specific elastic deficiency. This may explain the high frequency of CDH in URDS as compared to other varieties of CL.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on de novo copy number variations (CNVs) have not yet shown an association between an excess of chromosome 9 and CDH. However, several genes, such as ABL1, TLN1, PLPP6, and NOTCH1 were reported to be associated with CDH as a de novo variant in chromosome 9 [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic genetic alterations-both in complex and in isolated CDH-are associated with a worse prognosis (33). Moreover, de novo pathogenic alterations are seen more often in complex CDH (34)(35)(36). Phenotypical complex patients could be more likely to receive a genetic test.…”
Section: Isolated Cdh and Complex Cdhmentioning
confidence: 99%